Stress-controlled spin-wave modes of magnetic antivortices for superellipse-based magnonic devices - Escrig-Murua, J; Saavedra-Díaz, E (AIP Publishing, 2026)
We investigate the spin-wave dynamics of antivortices confined in superellipse-shaped FeGa nanostructures by means of micromagnetic simulations. Particular attention is given to the dynamic susceptibility and the spatial profiles of resonant modes under stress-induced anisotropy. Our results reveal a strong dependence of both the number and frequencies of resonance modes on the metastable magnetic state, governed jointly by geometry and applied stress. At zero stress, distinct radial and edge modes are identified, while tensile and compressive stresses induce additional peaks, mode splitting, and asymmetries in the antivortex core position. An abrupt change in the mode structure near critical stress values signals a transition from the antivortex to alternative magnetic configurations. These findings provide fundamental insights into the interplay between stress, geometry, and spin-wave dynamics and open avenues for the design of stress-tunable, high-frequency spintronic and magnonic devices with potential applications in flexible and reconfigurable microwave technologies.